Brand preferences between Apple and Samsung smartphone among UiTM students / Nurashikin Mohd Zaidi - Mohd Zaidi, Nurashikin (2015)
This study aim to investigate how the factors such as product performances affect the choices of brand preferences between Apple and Samsung. Nowadays smartphone is a must have gadget especially for students, so there is a crucial need for the company to distinguish themselves from the competitors. This study focus on 1) To examine the factors that affect the brand preferences for UiTM students between Apple and Samsung smart phone. 2) To determine the students preferences between Apple and Samsung smart phone. Correlation analysis and frequency analysis will be using in this research.